Development of a Salutogenesis Workshop for SPPs to Help Them, Their Athletes, and the Athlete’s Entourage Better Cope With Uncertainty During the COVID-19 Pandemic - Leisterer, Sascha; Lautenbach, Franziska; Walter, Nadja; Kronenberg, Lara; Elbe, Anne-Marie (Frontiers in Psychology, 2021)
The COVID19 pandemic is also called a crisis of uncertainty because of so many unforeseeable events like cancelled qualification competitions, loss of training facilities and postponement of the Olympic games. Athletes and their entourage experience this uncertainty as stressful. Sport psychology practitioners (SPPs) are in a key position to support athletes in coping with these unforeseeable stressors. However, SPPs are similarly affected by the COVID19 pandemic and simultaneously have to cope with stress. Salutogenesis, which describes how to manage stress and to stay well, provides a theoretical approach on how to cope with uncertainty. The salutogenetic approach aims at strengthening individuals’ sense of coherence (SoC) and consists of three components, namely comprehensibility, manageability, and meaningfulness. Although it is known that the SoC can be enhanced via psychological skills training so far this approach has not been systematically applied to the elite sport context. Furthermore, SPPs claim having a lack of knowledge on how to cope with uncertainty. The aim of this contribution is to outline how the salutogenetic approach can be applied to strengthening SPPs’ SoC via a single day four-part workshop. We outline how this workshop might help strengthen SPPs’ SoC and at the same time empower them to strengthen their athletes’ SoC. Overall, we add a theoretical (i.e., Salutogenesis in sports) and a practical perspective (i.e., coping techniques based on Salutogenesis) on how to cope with the COVID19 pandemic for SPPS, athlete’s and their support network.